PERANAN HUMAS PEMDA KOTA PALU PADA EVENT FESTIVAL PESONA PALU NOMONI DALAM MENJAGA CITRA KOTA PALU - Sampoerno, Aldimas Dwi (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
Palu City at the Palu Nomoni Festival event in maintaining the image of Palu City.The Palu Nomoni Festival Event has been held in two editions in 2016 and 2017 in Palu City. In those two editions things were still found which were feared to damage the image of Palu City as the host of the event. How does government public relations play a role in maintaining the image of Palu City at the event. The type of research that will be used in this research is qualitative descriptive research, namely research that aims to make a systematic, factual and accurate description that describes the events that occur in the field, related to the role of the local government of Palu City at the Palu Nomoni Festival event. The subjects of this study were 4 (four) informants with the consideration that the appointed informants were representatives who could provide accurate information in accordance with the needs and objects of the study. There are 4 (Four) roles of public relations according to Dozier and Broom which are key research theories The results of the study show that out of the 4 (Four) theories of public relations roles only 2 (two) are run quite well so that it can be said that public relations efforts in maintaining the image of Palu City regarding the image of the Palu Nomoni Festival have not been optimal.